2019
DOI: 10.1042/bcj20180922
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of the structural and functional architecture of encapsulated ferritins in bacteria and archaea

Abstract: Ferritins are a large family of intracellular proteins that protect the cell from oxidative stress by catalytically converting Fe(II) into less toxic Fe(III) and storing iron minerals within their core. Encapsulated ferritins (EncFtn) are a sub-family of ferritin-like proteins, which are widely distributed in all bacterial and archaeal phyla. The recently characterized Rhodospirillum rubrum EncFtn displays an unusual structure when compared with classical ferritins, with an open decameric structure that is enz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 30 publications
0
47
0
1
Order By: Relevance
“…3 In addition, prior native MS studies have also revealed that the EncFtn from the halophile Haliangium Ochraceum exists as a dynamic structure in multiple even-numbered oligomerisation states (dimer, tetramer, hexamer and decamer). 9 This observation implies that higher order oligomers are formed by the association of dimer units; presumably either via FOC dimer association, or non-FOC dimer association ( Fig. 1D and E).…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…3 In addition, prior native MS studies have also revealed that the EncFtn from the halophile Haliangium Ochraceum exists as a dynamic structure in multiple even-numbered oligomerisation states (dimer, tetramer, hexamer and decamer). 9 This observation implies that higher order oligomers are formed by the association of dimer units; presumably either via FOC dimer association, or non-FOC dimer association ( Fig. 1D and E).…”
mentioning
confidence: 88%
“…As previously reported, native MS analysis of Hoch-WT reveals a series of oligomerisation states. 9 The major species is dimer (+9 to +11) ( Fig. 2A, green circles), with some tetramer (13+ to 15+), hexamer (17+ to 18+) and decamer (22+ to 25+) species also observed ( Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…S2). 14,30 Unlike ferritin cages with higher symmetries, Flp cargo proteins cannot store precipitated iron in a soluble form by themselves and rely on the encapsulin shell to achieve iron precipitate sequestration. Similar to the ubiquitous ferritin iron storage cages, Flp encapsulin systems might play a dual role in oxidative stress resistance and iron homeostasis.…”
Section: Family 1 -Classical Encapsulinsmentioning
confidence: 99%
“…1A). 3,9 This is formed from a pentamer of dimers, the topology of which results in two distinct dimer interfaces. One dimer is structurally similar to the four helix-bundle of the classical ferritin monomer 9 and is formed by the two main helices of two EncFtn monomers.…”
mentioning
confidence: 99%